Clinical, genetic and confounding factors determine the dynamics of the in vitro response/non response to clopidogrel - Gremmel, Thomas; Panzer, Simon (Thrombosis and Haemostasis, 2011)
Platelet inhibition by clopidogrel varies from one individual to the next. Further, in vitro high on-treatment residual adenosine-diphosphate inducible platelet reactivity (HRPR) is associated with an increased risk for major adverse cardiovascular events after percutaneous coronary intervention (PCI) with stent implantation. Recent studies identified numerous influencing factors for the antiplatelet effect of clopidogrel. Besides genetic predispositions, diverse clinical conditions as well as pharmacological interactions were shown to significantly impair clopidogrel-mediated platelet inhibition. Consequently, these influencing factors may affect clinical outcome after PCI and it is therefore desirable to identify cofounders of HRPR by platelet reactivity testing. It is apparent, that not all assays are sensitive to the same variables, and only cofounders of HRPR that are repeatedly identified by more than one test system may be clinically meaningful. However, treatment adjustment based on platelet function testing has not been associated with improved patients’ outcome. This summary shall provide an overview over current knowledge on influencing factors for clopidogrel-mediated platelet inhibition and aid guidance for critical interpretation of in vitro obtained data on HRPR.
Keywords: Clopidogrel; platelet function testing; influencing factors